Perlindungan Hukum Bagi Pelaku Usaha Terhadap Tindakan Pembatalan Pembayaran Oleh Konsumen E-Commerce Dalam Sistem Cash on Delivery (COD) Menurut Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Muharram Wibisana; Jeane Neltje; Diana Fitriana (KRTHA BHAYANGKARA, 2023)
Marketplaces in Indonesia have offered a new payment system, namely Cash on Delivery (COD) to make it easier for consumers to make payments without having to have a bank account or go to an ATM to make transfers. COD is an electronic transaction system that is given in cash via courier as a third party when delivering goods to consumers. However, often COD provides a loss for the seller where there are buyers who are not responsible for making payments because buyers cannot be contacted and are not honest in providing information. The lack of legal regulation regarding the protection of business actors causes losses for business actors in running their business, especially in the COD payment system. By using normative juridical research methods, this study will discuss the payment system for e-commerce transactions between consumers and business actors as well as protection for business actors if consumers cancel e-commerce transactions in the cash on delivery payment system. The purpose of this study is to explain the payment system between consumers and business actors in e-commerce transactions and to analyze the protection for business actors in the event of cancellation of e-commerce consumer transactions in the cash on delivery system. The problem that the author will raise in this research is what factors cause business actors to be disadvantaged in the practice of cash on delivery (COD) payments, as well as legal protection for business actors who are harmed by consumers in the cash on delivery (COD) payment system in the e-commerce. Regarding the rights and obligations of consumers, it is regulated in Law Number 8 of 1999, which requires consumers to have good faith in transactions to buy goods and services, and consumers are also required to exchange according to the agreed wage exchange rate. The low understanding of consumers regarding COD payment methods in the marketplace causes losses for business actors. E-commerce need to be responsible for ix providing education about the online buying and selling process, including the COD payment system to the public.